Innovative Methods and Strategies for Effective Teaching and Learning - Modebelu, M.N; Duvie, A.N. (Mediterranean Journal of Social Sciences, 2012)
Teaching is an enabling job, a noble activity and a profession that involves a lot of activities to facilitatethe process. Learning, which is a positive permanent change in behaviour occurs through an effectiveteaching process. Effective teaching and learning centre on the teacher who is both the fulcrum on whicheducation revolves and the key that unlocks this door of education. Teachers in the third world nationsshould be fully equipped for this duty. The paper examines the innovative teaching methods for effectiveteaching and learning. Specifically the paper discusses: concept of effective teaching and learning,impediment to effective teaching and learning, enhancement factors, innovative teaching methods andconclusion. Recommendations include empowering teachers through quality workshops on application ofthe four innovative teaching methods viz: information transition and reception, cognitive strategiesdevelopment methods, attitude development methods and cognitive and motor skills developmentmethods.